Characterization and assessment of lung and bone marrow derived endothelial cells and their bone regenerative potential - Moraes de Lima Perini, Mariana; Valuch, Conner R.; Dadwal, Ushashi C.; Awosanya, Olatundun D.; Mostardo, Sarah L.; Blosser, Rachel J.; Knox, Adam M.; McGuire, Anthony C.; Battina, Hanisha L.; Nazzal, Murad; Kacena, Melissa A.; Li, Jiliang (Frontiers in Endocrinology, 2022)
Angiogenesis is important for successful fracture repair. Aging negatively affects the number and activity of endothelial cells (ECs) and subsequently leads to impaired bone healing. We previously showed that implantation of lung-derived endothelial cells (LECs) improved fracture healing in rats. In this study, we characterized and compared neonatal lung and bone marrow-derived endothelial cells (neonatal LECs and neonatal BMECs) and further assessed if implantation of neonatal BMECs could enhance bone healing in both young and aged mice. We assessed neonatal EC tube formation, proliferation, and wound migration ability in vitro in ECs isolated from the bone marrow and lungs of neonatal mice. The in vitro studies demonstrated that both neonatal LECs and neonatal BMECs exhibited EC traits. To test the function of neonatal ECs in vivo, we created a femoral fracture in young and old mice and implanted a collagen sponge to deliver neonatal BMECs at the fracture site. In the mouse fracture model, endochondral ossification was delayed in old control mice compared to young controls. Neonatal BMECs significantly improved endochondral bone formation only in aged mice. These data suggest BMECs have potential to enhance aged bone healing. Compared to LECs, BMECs are more feasible for translational cell therapy and clinical applications in bone repair. Future studies are needed to examine the fate and function of BMECs implanted into the fracture sites.